2019
DOI: 10.1183/23120541.00045-2019
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of home-based pulmonary rehabilitation in patients with fibrotic idiopathic interstitial pneumonias

Abstract: BackgroundFew studies have examined the benefits of pulmonary rehabilitation in patients with fibrotic idiopathic pulmonary pneumonia (f-IIP). Here, we report the results of an observational study in routine clinical practice of home-based pulmonary rehabilitation for f-IIP patients.MethodsA total of 112 consecutive patients (61 with idiopathic pulmonary fibrosis and 51 with fibrotic nonspecific interstitial pneumonitis) were enrolled, of whom 65 had mild-to-moderate disease (forced vital capacity (FVC) ≥50% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 39 publications
3
52
1
1
Order By: Relevance
“…Another issue is one associated with individualisation and standardisation of the rehabilitation programme, taking into account the patient's capabilities and preferences and resulting, among others, from the degree of functional impairment, need for oxygen therapy and comorbidities. Another controversial question is that of the duration of the effects of rehabilitation, since many authors claim that the effects last up to 6 [307,313,321], 11 [326] or even 12 months [325] after completing the programme, while others do not confirm its lasting beneficial effects in a longer term [315,321]. Lack of unequivocal data confirming distant effect indicates it is necessary to use rehabilitation in a continuous and systematic way.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Another issue is one associated with individualisation and standardisation of the rehabilitation programme, taking into account the patient's capabilities and preferences and resulting, among others, from the degree of functional impairment, need for oxygen therapy and comorbidities. Another controversial question is that of the duration of the effects of rehabilitation, since many authors claim that the effects last up to 6 [307,313,321], 11 [326] or even 12 months [325] after completing the programme, while others do not confirm its lasting beneficial effects in a longer term [315,321]. Lack of unequivocal data confirming distant effect indicates it is necessary to use rehabilitation in a continuous and systematic way.…”
Section: Commentarymentioning
confidence: 99%
“…Attempts should be made to continue the programme at home. Supervised home rehabilitation, with optional use of telemedicine, can be an alternative to the traditional method [325].…”
Section: Introductionmentioning
confidence: 99%
“…According to one meta‐analysis, inpatient rehabilitation specifically designed for older adults potentially improves physical function and mortality outcomes 5 . Pulmonary rehabilitation, an intervention that includes exercise training, is beneficial for patients with chronic interstitial lung disease 6 . Early rehabilitation has been shown to contribute to decreasing in‐hospital mortality in patients with chronic obstructive pulmonary disease (COPD) in the acute care setting 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Authors: Baptiste Chéhère a,b , Jean-Marie Grosbois c,d , Cécile Chenivesse e , Benoit Wallaert d,e and Valérie Bougault a,f . We previously reported the results of an 8-week home-based pulmonary rehabilitation (PR) program in patients with fibrotic interstitial idiopathic pneumonia (f-IIP), which demonstrated significant long-term (12 month) improvements in exercise capacity, anxiety, and quality of life [1]. However, most studies of f-IIP patients have shown that the benefits are lost within 6 to 9 months after the PR program [2], largely due to a failure to continue with exercise training [3].…”
mentioning
confidence: 99%
“…week supervised PR program, as previously described [1,4], were recruited to this pilot study, The baseline values (before the home-based PR program) were: age 65±9 years, FVC 75±13% predicted, FEV 1 73±12% predicted, and DLCO 40±8% predicted (means ± standard deviations). Eleven subjects selected the local facility maintenance program (APA group) and 8 preferred to continue exercising at home (control group) ( Figure 1).…”
mentioning
confidence: 99%